2015
DOI: 10.2141/jpsa.0140114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics on the Expression and Localization of Avian β-defensins in the Proventriculus of Broiler Chicks

Abstract: The aim of this study was to determine the effects of probiotics-feeding on the gene expression and protein localization of avian β-defensins (AvBDs) in the proventriculus of broiler chicks. Male broiler chicks were arranged in 3 groups: control group, probiotics group I and probiotics group II, which were fed with starter rations containing 0%, 0.2% or 0.4% probiotics, respectively, from day 0 (D0; at one day old) to D14. Proventriculi in all groups were collected at D0, D7 and D14 for analysis of AvBDs expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…The expression levels of any CATHs with no LPS challenge was not higher in the P-group than in non-P-group in both the proventriculus and cecum, and CATH1 expression in the cecum was lower in the Pgroup than in non-P-group in Experiment 2. These results suggest that probiotics themselves did not upregulate CATHs expression as reported for the AvBDs expression in the proventriculus (Mohammed et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The expression levels of any CATHs with no LPS challenge was not higher in the P-group than in non-P-group in both the proventriculus and cecum, and CATH1 expression in the cecum was lower in the Pgroup than in non-P-group in Experiment 2. These results suggest that probiotics themselves did not upregulate CATHs expression as reported for the AvBDs expression in the proventriculus (Mohammed et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
“…The effects of probiotics may be weak in the proventriculus since the probiotics bacteria may not be able to adapt and proliferate in the acidic medium of the proventriculus. We have reported that probiotics-feeding did not affect the expression of AvBD12, wherease the AvBD12 protein density in the surface epithelial cells was lowered by probiotics-feeding, suggesting that they were secreted more in chicks fed with probiotics (Mohammed et al, 2015). Although the exact reason why LPS did not affect the CATHs expression in the proventriculus in both P-and non-P-groups is not known, we assume that mucous substances on the mucosal surface protected the tissue from binding of LPS.…”
Section: Discussionmentioning
confidence: 82%
“…However, their expression was not enhanced upon k-ST stimulation or LR treatment. Our pre-vious results showed that AvBD2 and AvBD7 expression in the proventriculus of broiler chicks was not altered by the probiotic feed, that included Streptococcus faecalis, Clostridium buthricum, and Bacillus mesentericus (Mohammed, et al, 2015). Thus, oral administration of LR and ST stimulation, as in this study, may not affect the expression of AvBD2 and AvBD7 in the intestine.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, birds in the LR group showed reduction in the expression of AvBD10 in the ileum and cecum, and that of AvBD12 in the crop. We have previously reported that probiotic bacteria, including Streptococcus faecalis, Clostridium butyricum, and B. mesentericus lowered AvBD12 protein level in the proventriculus of broiler chicks (Mohammed et al, 2015). Akbari et al (2008) reported that probiotic feeding did not change the expression of AvBDs in the cecal tonsil, but Salmonella infection did.…”
Section: Discussionmentioning
confidence: 94%
“…According to previous studies, these AvBDs can kill a broad range of microbes such as pathogenic bacteria, fungi, and virus (van Dijk et al, 2008;Cuperus et al, 2013). In our previous studies, several anti-microbial peptides, including AvBDs and cathelicidins, were identified in the mucosal tissue of male and female reproductive organs and in the intestinal mucosa (Mohammed et al, 2015;Yoshimura, 2015;Mohammed et al, 2016). Terada et al (2018) reported that AvBD expression and AvBD2 localization in the intestine changed dynamically before and after hatching, suggesting that AvBDs are important for host defense in the intestinal mucosa of embryos and neonatal chicks.…”
Section: Introductionmentioning
confidence: 83%